PEMAFAATAN KULIT UDANG DAN CANGKANG KEPITING SEBAGAI BAHAN BAKU KITOSAN - Diana Purnama Sari; Ira Maya Abdiani (Jurnal Harpodon Borneo, 2015)
Processing of crustaceans especially shrimp and crab is a process that keep on progressing years to years. This condition will also followed by the increasing of shrimp shell waste, shrimp head and crab shell. Meanwhile, the processing of shrimp and crab shell is still limited in Tarakan. This research intended to know of the content chitosan of shrimp and crab shell. The research method that is used in this research was descriptive analysis of shrimp shell waste and crab shell with four times repetition. The result showed that the highest yield chitosan in crab shell was 46.30% and the lowest yeild chitosan in shrimp shell was 30.63%. Based on the result of water content analysis, the highest value in shrimp shell was 6.94% 10% and the lowest water content in crab shell was 6.78% 10%.   Keywords: shrimp shell waste, crab shell, yield, and water content.